2008
DOI: 10.1097/ta.0b013e3181454a05
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Response After Resuscitation With Hemoglobin-Based Oxygen Carrier and Recombinant Factor VIIA in Uncontrolled Hemorrhagic Shock in a Swine Model

Abstract: HBOC-201 + rfVIIa triggered minimum immune activation in an uncontrolled HS swine and there was a nonsignificant survival benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Arnaud et al in a preclinical study showed that transfusion of HBOC-201 successfully resuscitated and avoided blood transfusion in animals, but it caused dilutional coagulopathy (lower hematocrit, platelets, and fibrinogen) ( 66 ). HBOC-201 combined with other coagulation substances such as freeze-dried plasma (FDP) ( 67 ) or recombinant coagulation factor VIIa (rfVIIa) that had little effect on functional coagulation indicators and had no significant survival benefit ( 68 ). However, in the combination of a bleeding model with the Folts model, due to the interaction of many factors such as platelet count, hematocrit, and platelet aggregation, HBOC-201 can reduce thrombosis ( 69 ).…”
Section: Trauma and Hemorrhagic Shockmentioning
confidence: 99%
“…Arnaud et al in a preclinical study showed that transfusion of HBOC-201 successfully resuscitated and avoided blood transfusion in animals, but it caused dilutional coagulopathy (lower hematocrit, platelets, and fibrinogen) ( 66 ). HBOC-201 combined with other coagulation substances such as freeze-dried plasma (FDP) ( 67 ) or recombinant coagulation factor VIIa (rfVIIa) that had little effect on functional coagulation indicators and had no significant survival benefit ( 68 ). However, in the combination of a bleeding model with the Folts model, due to the interaction of many factors such as platelet count, hematocrit, and platelet aggregation, HBOC-201 can reduce thrombosis ( 69 ).…”
Section: Trauma and Hemorrhagic Shockmentioning
confidence: 99%
“…A suitable biological system is the in vitro evaluation of these potential blood substitutes on human peripheral blood mononuclear cells. Indeed, once transfused into the blood vessels, blood substitutes will encounter lymphocytes, monocytes and other cells, implicated in the cellular immune response (Malkevich et al 2008). Another useful test system has previously been shown to be the culture of human umbilical vein cord cells.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo, os valores de IL-10 obtidos foram muito baixos ao longo do período de observação embora um aumento significante nos grupos HNA + Gel e HNA + NaCl foram verificados 60 minutos depois da HNA com valores médios de 59±11 pg/ml, valor que pode ser considerado normal para esta citocina nas medidas basais Nielsen et al, 2007;Malkevich et al, 2008). No estudo de Lee et al (2005) observou-se níveis de IL-10 em torno de 250 pg/ml no final da ressuscitação com gelatina e no grupo Sham.…”
Section: Grupo Controleunclassified